Profile of patients undergoing therapy using botulinum toxin within the late neurorehabilitation of adult post-stroke patients - Emilia Mikołajewska; Jarosław Tywoniuk (Kazimierz Wielki University, 2015)
Mikołajewska Emilia, Tywoniuk Jarosław. Profile of patients undergoing therapy using botulinum toxin within the late neurorehabilitation of adult post-stroke patients. Journal of Education, Health and Sport. 2015;5(8):318-321. ISSN 2391-8306. DOI 10.5281/zenodo.28934 http://dx.doi.org/10.5281/zenodo.28934 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A318-321 https://pbn.nauka.gov.pl/works/611586 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-f9b4bd83-e84b-4888-9acb-5b71eb387186 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015.   Profile of patients undergoing therapy using botulinum toxin within the late neurorehabilitation of adult post-stroke patients   Emilia Mikołajewska1,2,3, Jarosław Tywoniuk2   1 Department of Physiotherapy, Ludwik Rydygier Collegium Medium in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland 2 Rehabilitation Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland 3 Neurocognitive Laboratory, Interdisciplinary Center for Modern Technologies, Nicolaus Copernicus University in Toruń, Poland   Corresponding author: Emilia Mikołajewska Rehabilitation Clinic Military Clinical Hospital No. 10 and Polyclinic Powstańców Warszawy 5 85-681 Bydgoszcz, Poland e-mail: e.mikolajewska@wp.pl, emiliam@cm.umk.pl www: http://emikolajewska.netstrefa.eu   Keywords: neurorehabilitation; physiotherapy; stroke; spasticity; botulinum toxin.   Abstract   BACKGROUND: Scientists and clinicians still look for satisfactory treatment for post-stroke spasticity, especially within long-term neurorehabilitation. Relatively novel therapeutic method is use of botulinum toxin type A (BTX-A). OBJECTIVE: Contrary to the previous studies we focused on late post-stroke population. This study aims at showing such patients profiles. CASE STUDIES PRESENTATION: We decribe a convenience sample cases study analysis of six adult patients with post-stroke spasticity (mean time after cerebrovascular accident: 7.5 years) admitted to the neurological rehabilitation ward. CONCLUSIONS: Despite BTX-A is one of the most potent antispastic medications details of its optimal application and effectiveness within long-term naurorehabilitation of adults are still in the process of being confirmed. Current health status, secondary changes and complications, individual therapeutic goals and functional skills expected to achieve in particular case may significantly modify way of the therapy.